2019
DOI: 10.1002/jcph.1379
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Gene‐Environment Interaction Terms Improved the Predictive Accuracy of Tacrolimus Stable Dose Algorithms in Chinese Adult Renal Transplant Recipients

Abstract: The narrow therapeutic window of tacrolimus necessitates daily monitoring and predictive algorithms based on genetic and nongenetic factors. In this study, we constructed predictive algorithms for tacrolimus stable dose in a retrospective cohort of 1045 Chinese renal transplant recipients. All patients were genotyped for CYP3A4 20230T>C (rs2242480), CYP3A4 T>C (rs4646437), CYP3A5*3 6898A>G (rs776746), ABCB1 129T>C (rs3213619); ABCB1 c.1236C>T (rs01128503), ABCB1 c.2677G>T/A (rs2032582) and ABCB1 c.3435C>T (rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Several studies have suggested the conflicting roles of CYP3A4 *1G in CYP3A4 activity. CYP3A4 *1G polymorphism enhances the disposition of CYP3A4 substrates, including atorvastatin ( Gao et al, 2008 ), cyclosporin A ( El-Shair et al, 2019 ), and tacrolimus ( Tamashiro et al, 2017 ; Tang et al, 2019 ). In contrast, CYP3A4 *1G polymorphism is reported to decrease the disposition of fentanyl ( Yuan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the conflicting roles of CYP3A4 *1G in CYP3A4 activity. CYP3A4 *1G polymorphism enhances the disposition of CYP3A4 substrates, including atorvastatin ( Gao et al, 2008 ), cyclosporin A ( El-Shair et al, 2019 ), and tacrolimus ( Tamashiro et al, 2017 ; Tang et al, 2019 ). In contrast, CYP3A4 *1G polymorphism is reported to decrease the disposition of fentanyl ( Yuan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in CYP3A4, such as the single nucleotide polymorphism (SNP) CYP3A4*22 (rs35599367, G>A) in intron 6, which affects its transcript splicing, decreases CYP3A4 expression (Wang and Sadee, 2016), resulting in improved pharmacokinetics and clinically effective therapy (Wang et al, 2011Mulder et al, 2021. The intronic genetic variation in CYP3A5, CYP3A5*3 (rs776746, A>G), leads to decreased normal CYP3A5 expression through alternative splicing (Kuehl et al, 2001) and is associated with tacrolimus dosage and pharmacokinetics (Dorr et al, 2017;Tang et al, 2019). Recently these two SNPs have become biomarkers for clinical individualized medications.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of machine learning and deep learning techniques, more studies applied these techniques to enhance the model expression of the complicated relationship between individual factors and medication dose. Tang et al first applied multiple machine learning algorithms to establish a stable dosing prediction model of tacrolimus in Chinese KTRs, and proved the method was superior to the MLR ( 20 , 21 ). In addition to the algorithms used in Tang's research, some algorithms with more sophisticated principles were developed, such as eXtreme Gradient Boosting (XGBoost), light gradient boosting machine (LightGBM), Categorical Boosting (CatBoost), random forest (RF), and TabNet (a deep learning technique), which were highly recognized in the algorithm competitions ( 22 – 26 ).…”
Section: Introductionmentioning
confidence: 99%